Respuesta :

Answer:

You will need to use simultaneous equations.

Method:

First we need to make one set of variable the same, in this case we will:

-Multiply the top equation by 3 to get 6x
-Multiply the bottom equation by 2 to get 6x

The result will be as follows:

1) 2x+5y=-13 x3
1) 6x+15y=-39

2) 3x-4y=-8 x2
2) 6x-8y=-16

Now we will make both equations equal to 6x:

1) 6x=-15y-39
2) 6x=8y-16

Now because they both equal 6x, they therefore equal each other:

-15y-39=8y-16
-23=23y
y=-1

Now that we have y, we can substitute it back into one of the equations to get x:

1) 2x+5(-1)=-13
2x-5=-13
2x=-8
x=-4